2514. Pediatric Medically Attended Shingles in Alberta, Canada 2016; Preliminary Results. (26th November 2018) - Booth, Stephanie; Russell, Margaret L; McDonald, Bruce M; Simmonds, Kimberley A; Svenson, Lawrence W; Bell, Christopher A; Malo, Shaun; Dover, Douglas C
Abstract: Background: Herpes zoster (shingles) is a reactivation of latent varicella virus. Shingles is uncommon in children and children vaccinated against varicella may be at a reduced risk of shingles. Alberta has a publicly funded healthcare system and added publicly funded varicella vaccine to the routine childhood vaccination schedule in 2001. Methods: We used provincially held administrative health databases to examine the epidemiology of incident shingles cases in children under the age of 19. Incident shingles cases were defined as the earliest record of ICD-9-CM 053 OR ICD-10-CA B02 coded physician claims, hospital, or emergency room visits between 1985 and 2016, with incident cases in this cohort occurring between January 1, 2016 and December 31, 2016. Varicella immunization was identified through Alberta's immunization repository and immunosuppressive comorbid conditions (neoplasms, HIV/AIDS, cystic fibrosis, and immune system disorders) were identified using ICD diagnostic codes from physician claims, hospital, or emergency room visits and Alberta's Communicable Disease Control databases. Results: 1, 003 incident shingles cases were identified in children under the age of 19 in 2016, a crude rate of 0.98/1, 000 persons. Females comprised 54% of cases. The largest proportion of cases occurred among those aged 15–19 years. About 39% of cases were prescribed antiviral medication, most commonly those aged 15–19 years. The crude rate per 1, 000 population increased with age: 0.5 for children under the age of 1, 1.2 for those 1–4 years, 1.25 for children 5–9 years, 2.19 for children 10–14 years, and 3.7 for children aged 15–19 years. Crude rates were similar among both males and females. Less than 3% of the cases had ever been immunized against varicella. Shingles diagnostic codes were not validated, which likely led to an overestimation of the true rates of disease. Conclusion: Additional studies are needed on pediatric shingles cases and factors that influence shingles in this group, as well as validation studies of ICD diagnostic coding in administrative data. Disclosures: M. L. Russell, Novartis Pharmaceuticals Canada Inc.: Grant Investigator and Unconditional Research Grant, Grant recipient. Merck Frosst Canada Inc.: Grant Investigator and Unconditional Research Grant, Grant recipient.